2021
DOI: 10.1039/d0fo03264f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity and mechanism of trilobatin on tyrosinase: kinetics, interaction mechanism and molecular docking

Abstract: Tyrosinase is the rate-limiting enzyme controlling the production of melanin, and tyrosinase inhibitors can regulate the overproduction of melanin by inhibiting tyrosinase activity, which is an effective method to treat...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
6
11
0
Order By: Relevance
“…Thus, both substrate and inhibitor could attach to the enzyme simultaneously in two different sites dependently, and the degree of inhibition affected by the change in the substrate concentration is dependent on the interaction between the two sites of substrate and inhibitor (Saboury, 2009). This same inhibition type has also been found in previous studies, in which epigallocatechin‐3‐gallate, gallocatechin gallate, homoisoflavonoids and trilobatin inhibited the diphenolase activity of tyrosinase (Song et al, 2021; Wang et al, 2021; Yu et al, 2021). These results suggest that the monophenolase and diphenolase activities of tyrosinase respond to one active site only during the three different stages of oxidation (Sánchez‐Ferrer et al, 1995).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Thus, both substrate and inhibitor could attach to the enzyme simultaneously in two different sites dependently, and the degree of inhibition affected by the change in the substrate concentration is dependent on the interaction between the two sites of substrate and inhibitor (Saboury, 2009). This same inhibition type has also been found in previous studies, in which epigallocatechin‐3‐gallate, gallocatechin gallate, homoisoflavonoids and trilobatin inhibited the diphenolase activity of tyrosinase (Song et al, 2021; Wang et al, 2021; Yu et al, 2021). These results suggest that the monophenolase and diphenolase activities of tyrosinase respond to one active site only during the three different stages of oxidation (Sánchez‐Ferrer et al, 1995).…”
Section: Resultssupporting
confidence: 85%
“…Previous studies have similarly reported that hesperidin inhibited tyrosinase activity by only approximately 5% when L‐dopa was used as the substrate (Zhang et al, 2007). In addition, more recent reports found that hesperetin, naringenin, neohesperidin and naringin exhibited no distinct inhibition of the diphenolase activity of tyrosinase, resulting in the catalyzation of L‐dopa to Dopa quinone (Yu et al, 2021). Thus, hesperetin, naringenin, neohesperidin and naringin mainly inhibit the monophenolase activity of tyrosinase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations